Corporate Finance - Nguyen, Xuan Hai (Khoa Quốc tế, ĐHQGHN, 2020)
This module is intended to introduce you to the ideas and techniques of running a financially successful business. In order to grow and expand, businesses must both find profitable investments and obtain funds to make those investments. This module aims to give you the tools and skills you need to do those two things and to develop your understanding of the concepts and principles on which good financial decisions are based.